1997
DOI: 10.2307/3433301
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the K-ras and p53 Genes in Rat Lung Tumors

Abstract: Activation of the K-ras protooncogene and inactivation of the p53 tumor suppressor gene are events common to many types of human cancers. Molecular epidemiology studies have associated mutational profiles in these genes with specific exposures. The purpose of this paper is to review investigations that have examined the role of the K-ras and p53 genes in lung tumors induced in the F344 rat by mutagenic and nonmutagenic exposures. Mutation profiles within the K-ras and p53 genes, if present in rat lung tumors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Multiple mutations due to the presence of O 2 -POB-T have been reported (Sharma et al, 2008). Mutations have not been reported in K-ras and p53 genes isolated from rat lung tumors induced by NNK, so the relative impact of these miscoding events is unclear (Belinsky et al, 1997).…”
mentioning
confidence: 99%
“…Multiple mutations due to the presence of O 2 -POB-T have been reported (Sharma et al, 2008). Mutations have not been reported in K-ras and p53 genes isolated from rat lung tumors induced by NNK, so the relative impact of these miscoding events is unclear (Belinsky et al, 1997).…”
mentioning
confidence: 99%
“…Studies showed the p53 protein was not present in any normal human mucosas tested but was detected at an increasing rate, in squamous tumors of various stages of development (Boorman et al, 1996). Unlike the human, the rat had no detectable p53 mutations following CB exposure (Belinsky et al, 1997;Swafford et al, 1995).…”
Section: Analysis Of Tumorsmentioning
confidence: 93%
“…K-ras point mutations have been found however to be early markers of lung adenocarcinomas and squamous cell carcinomas following exposure to various agents other than CB (Belinsky et al, 1997).…”
Section: Analysis Of Tumorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Detection of K-ras mutations: A mutant codon 12 K-ras PCR enrichment restriction fragment length polymorphism (RFLP) analysis was used to detect K-ras mutations in the soft tissue tumors (Belinsky et al, 1996(Belinsky et al, , 1997Nickell-Brady et al, 1994). The assay relies on the construction of the K-ras 5' first exon primer where the G residue at the first position of codon 11 is replaced with a C. Amplification of a wild-type K-ras allele using this primer 13 creates gene fragments harboring a BstNl restriction enzyme cleavage site (CCTGG)…”
Section: Analyses Of K-ras Codon 12 Mutationsmentioning
confidence: 99%